2012
DOI: 10.1021/ma3017585
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Isobutylene by GaCl3 or FeCl3/Ether Complexes in Nonpolar Solvents

Abstract: The carbocationic polymerization of isobutylene (IB), co-initiated by GaCl 3 or FeCl 3 ·dialkyl ether 1:1 complexes has been investigated in hexanes in the −20 to 10°C temperature range. In contrast to AlCl 3 ·diisopropyl ether (AlCl 3 ·i-Pr 2 O) complexes, 1 GaCl 3 ·i-Pr 2 O and FeCl 3 ·i-Pr 2 O readily co-initiate polymerization with 2-chloro-2,4,4-trimethylpentane (TMPCl) or tert-butyl chloride (t-BuCl) in the presence or absence of proton trap. In the absence of proton trap, chain transfer to monomer readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 16 publications
3
79
0
Order By: Relevance
“…At higher temperature, the equilibrium constant of oxoniumcarbenium ion is lower and polymerization may proceed as has been reported by the AlCl 3 , 28,30 GaCl 3 25 and FeCl 3 20,24,25,31 complexes with i-Pr 2 O. In addition to temperature, steric and electronic effects influence the stability of oxonium ions.…”
Section: ■ Experimental Sectionmentioning
confidence: 59%
“…At higher temperature, the equilibrium constant of oxoniumcarbenium ion is lower and polymerization may proceed as has been reported by the AlCl 3 , 28,30 GaCl 3 25 and FeCl 3 20,24,25,31 complexes with i-Pr 2 O. In addition to temperature, steric and electronic effects influence the stability of oxonium ions.…”
Section: ■ Experimental Sectionmentioning
confidence: 59%
“…This is the first report on the synthesis of PTMG using anhydrous FeCl 3 without additional solvent. This catalyst is particularly promising for the scalable and economical production of PTMG because FeCl 3 is a relatively nontoxic, environmentally benign, and abundant reagent . Moreover, no halogenated by‐products, which are difficult to separate from PTMG and have a detrimental effect on the polymer properties, are formed during the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…This catalyst is particularly promising for the scalable and economical production of PTMG because FeCl 3 is a relatively nontoxic, environmentally benign, and abundant reagent. [23][24][25][26][27][28][29] Moreover, no halogenated by-products, which are difficult to separate Additional Supporting Information may be found in the online version of this article. from PTMG and have a detrimental effect on the polymer properties, are formed during the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…The exo‐olefin terminated PIB is also referred to as “highly reactive” PIB (HR PIB), since it readily reacts with maleic anhydride in a thermal “ene” reaction to produce PIB succinic anhydride that can be converted to polyisobutenylsuccinimide, used as ashless dispersants. In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB . Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application. [26][27][28] Recently, we reported an ethylaluminum dichloride (EADC)Ábis(2-chloroethyl) ether (CEE) complex as a fully hydrocarbon soluble catalyst that in conjunction with tert-butyl chloride (t-BuCl) initiator in hexanes at 0-20 8C gave HR PIB with quantitative yields and up to 92% exo-olefin end-functionality.…”
mentioning
confidence: 99%